Corporate Tax Saving Strategy and Share Price Performance (International Journal of Scientific Research and Management (IJSRM), 2023)
This study ascertained how corporate tax saving strategy affect share price performance. It examined how debt tax shield, non-debt tax shield, and effective tax rate affect share price performance. The secondary source of data collection was adopted in the study where the purposive sampling technique was used to select a sample size of twelve (12) listed industrial goods firms in Nigeria. Ordinary Least Square regression analysis was used in this study and the findings revealed that non-debt tax shield has significant effect on share price performance of listed industrial goods firms in Nigeria and that effective tax rate has significant effect on share price performance of listed industrial goods firms in Nigeria. The study concluded that crucial component of fiscal policy that has a great impact on both the social and economic development of a nation, hence, tax savings demands attention from managers at all levels of management. The study recommended that Nigerian government needs subsidize cost of debt-financing for the companies operating in the country’s capital market and that stakeholders should develop the financial markets and make it accessible for firms to obtain long-term financing for economic growth and development.